Association between elevated homocysteine levels and obstructive sleep apnea hypopnea syndrome: a systematic review and updated meta-analysis - He, Jie; Zhou, Haiying; Xiong, Juan; Huang, Yuanyuan; Huang, Na; Jiang, Jiaqing (Frontiers in Endocrinology, 2024)
Objective This study aimed to distinguish between healthy controls and patients with OSAHS regarding homocysteine (HCY) levels and investigate how individuals with OSAHS respond to continuous positive airway pressure ventilation (CPAP) in terms of serum and plasma HCY levels. Methods To ascertain published articles about OSAHS, an exhaustive search was performed across medical databases, encompassing PubMed, Web of Science, EMBASE, CNKI, and Cochrane Library, until January 2, 2024. This study reviewed the literature regarding HCY levels in individuals with OSAHS and control groups, HCY levels under pre- and post-CPAP treatment, the Pearson/Spearman correlation coefficients between HCY levels and apnea-hypopnea index (AHI), and the hazard ratio (HR) of HCY levels concerning the occurrence of major adverse cerebrocardiovascular events (MACCEs) in patients with OSAHS. Meta-analyses were performed using weighted mean difference (WMD), correlation coefficients, and HR as effect variables. The statistical analysis was conducted using the R 4.1.2 and STATA 11.0 software packages. Results In total, 33 articles were selected for the final analysis. The OSAHS group exhibited significantly higher serum/plasma HCY levels than the control group (WMD = 4.25 μmol/L, 95% CI: 2.60–5.91, P< 0.001), particularly among individuals with moderate and severe OSAHS. Additionally, subgroup analysis using mean age, ethnicity, mean body mass index, and study design type unveiled significantly elevated levels of HCY in the serum/plasma of the OSAHS group compared to the control group. CPAP treatment can significantly decrease serum/plasma HCY levels in patients with OSAHS. Moreover, elevated HCY levels in individuals with OSAHS could be one of the risk factors for MACCEs (adjusted HR = 1.68, 95% CI = 1.10–2.58, P = 0.017). AHI scores show a positive correlation with serum/plasma HCY levels. Conclusion Patients with OSAHS had elevated serum/plasma HCY levels compared to healthy controls; however, CPAP therapy dramatically decreased HCY levels in patients with OSAHS. In patients with OSAHS, elevated HCY levels were linked with an increased risk of MACCEs, and HCY was positively connected with AHI values. HCY levels may serve as a useful clinical indicator for determining the severity and efficacy of OSAHS treatments. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024498806.